Increases in interspecific but mixed trends in intraspecific body sizes in German stream macroinvertebrates across two decades - Mittag, David C.; Baker, Nathan J.; Antão, Laura H.; Kuczynski, Lucie; Haase, Peter; Welti, Ellen A. R. (Wiley, 2026)
The Anthropocene has accelerated changes both among and within species, altering the functional trait composition of ecological communities globally. Animal body sizes have broad implications for ecosystem structure and functioning, with the temperature–size rule predicting body size declines with warming. We measured individual macroinvertebrate body dimensions from the LTER site ‘Rhine-Main-Observatory' between 2001 and 2019 to test for changes in intraspecific biomass for nine common species representing different taxonomic groups. We further assessed changes in interspecific body size of whole macroinvertebrate communities and the relationships between interspecific body sizes and a given species' temporal trend in density across sites. Intraspecific changes in biomass over time were highly variable, with temperature only moderately predicting these trends. Specifically, species with strict univoltine life cycles showed no change over time, while four non-univoltine species experienced the strongest variation in intraspecific body size. In parallel, weighted means of interspecific body sizes of whole macroinvertebrate communities increased over time, with sites with warmer average temperatures being dominated by larger taxa, which also tended to have greater increases in density over time. Our findings do not align with previous predictions of widespread reductions in invertebrate body sizes with rising temperatures, suggesting the temperature–size rule may vary among taxonomic groups, levels of biological hierarchy (intra- versus interspecific), and across sites. Other environmental changes, such as improving water quality, may underlie or counteract shifts in body size, while only two of the sites in our study experienced temperature increases during the study period. Quantifying changes in animal body size within and between species – which is only possible through maintained long-term collections – provides key insights into the processes and dynamics of biodiversity change in a rapidly changing world, highlighting the complex dynamics of variation among species and sites, which preclude ‘fit-all' predictions of the effects of global change.